2021
DOI: 10.3390/ijerph18041455
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability-Sport-Physical Activity

Abstract: The present study is a synthesizing analysis of international literature on correlations between sustainability, sport, and physical activity. The study of sustainability is considered essential in modern research; its multidisciplinary approach relies on sports science and sports economics as well. There are several aspects of sustainability that are closely associated with health and health preservation; the beneficial effect of exercise on health is also widely known. For the analysis of this complex matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 133 publications
(172 reference statements)
1
11
0
2
Order By: Relevance
“…Their rates largely depend on the income situation of the region, as well as the prevalent social and cultural views. It is assumed that in places where the desire to increase sport activity is hindered by low income, it is extremely difficult to produce changes [ 46 ]. However, low-level physical activity results in a decline in people’s health and an increase in health expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Their rates largely depend on the income situation of the region, as well as the prevalent social and cultural views. It is assumed that in places where the desire to increase sport activity is hindered by low income, it is extremely difficult to produce changes [ 46 ]. However, low-level physical activity results in a decline in people’s health and an increase in health expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…The role of educational institutions for the elderly should be fulfilled by the Universities of the Third Age, established not only in large cities but also in small and rural areas. In turn, in sport, sports clubs and associations should be responsible for a nutritional strategy supervised and implemented by specialists in the field of sports nutrition [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that spending time actively by children promotes their physical, social and emotional development [ 59 ], and the appropriate amount and organization of urban recreational areas play a significant role in increasing recreational wellbeing, which is positively related to individuals’ physical well-being associated with happiness and life satisfaction [ 60 ]. Many studies indicate a positive correlation between physical activity and subjective well-being [ 61 , 62 ]. Sport may also protect against symptoms of mental disorders that are increasingly prevalent among adolescents [ 63 ].…”
Section: Discussionmentioning
confidence: 99%